Dumping Practices on Market Balance: A Review of Business Competition in E-Commerce - Laa Tansa Amalia; Rachel Luna Widyawati; Anintyas Kusuma; Amalia Nurwachidah Rosyadi (Journal of Law, Politic and Humanities, 2024)
The practice of dumping is an increasing phenomenon in international trade. Dumping is a practice where exporters sell commodities on the international market at prices below fair value or lower than the price in the country of origin or the general price on the international market. This practice is considered unfair because it can damage the market and harm competitors in the importing country. The government can adopt policies and regulations that protect local producers from dumping practices. Industry players can work together to monitor and report suspicious dumping practices. International institutions such as the World Trade Organization (WTO) can play an important role in addressing dumping practices by providing an international legal framework that regulates this practice. This research uses a normative juridical approach with analysis of various relevant laws, regulations and policies. It is hoped that the results of this research will provide a clearer understanding of the practice of dumping and the legal consequences it causes in the perspective of Law No. 5 of 1999 concerning Business Competition in Indonesia.